2006
DOI: 10.1002/ejsp.296
|View full text |Cite
|
Sign up to set email alerts
|

Emotional reactions to harmful intergroup behavior

Abstract: In this paper, we examined reactions to situations in which, although one is not personally involved, one could see oneself connected to either the perpetrators or the victims of unfair behavior. We manipulated participants' similarity and measured their identification to either one of two groups which participants later learned was the victim or the perpetrator of harmful behavior. As predicted, making salient similarities to the victims lead participants to: 1) appraise the perpetrator's behavior as more unf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
136
0
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(153 citation statements)
references
References 20 publications
11
136
0
6
Order By: Relevance
“…The main postulate of intergroup emotion theory is that when a social identity is salient, situations are appraised in terms of their consequences for the in-group, eliciting specific intergroup emotions and behavioural intentions. Thus people experience emotions on behalf of their group when the social category is salient and they identify with the group at stake (Devos et al, 2002;Gordijn et al, 2006). Klandermans, 2007).…”
Section: Emotionsmentioning
confidence: 99%
“…The main postulate of intergroup emotion theory is that when a social identity is salient, situations are appraised in terms of their consequences for the in-group, eliciting specific intergroup emotions and behavioural intentions. Thus people experience emotions on behalf of their group when the social category is salient and they identify with the group at stake (Devos et al, 2002;Gordijn et al, 2006). Klandermans, 2007).…”
Section: Emotionsmentioning
confidence: 99%
“…Gordijn, Yzerbyt, Wigboldus, and Dumont (2006) have found that manipulating whether or not a participant could relate to the victim or perpetrator influenced their judgments, intensity of anger and subsequent behaviors, in reaction to a scenario that described a harmful behavior that one group inflicted on another group. Specifically, when persons were reminded of their similarities to the victims, this increased their judgments of unfairness, increased their anger and made it more likely that they would take action toward the perpetrator.…”
Section: Disgust: Inflexibility Of Thoughtsmentioning
confidence: 99%
“…These negative emotions arise when people appraise in-group members as responsible for committing a salient illegitimate action (Shepherd, Spears, & Manstead, 2013a, 2013b. In-group directed anger, in particular, is an "other focused" emotion that is experienced when people attend to the victims of negative in-group behavior (e.g., Gordijn, Yzerbyt, Wigboldus, & Dumont, 2006;Iyer, Leach, & Crosby, 2003;Iyer, Schmader, & Lickel, 2007). Similarly, sympathy is an "other-focused" emotion that is felt when people focus on the victim's plight (Iyer et al, 2003).…”
Section: Assessing Convergent and Discriminant Validity Of The Mdishmentioning
confidence: 99%
“…These emotion items were adapted from Gordijn et al (2006) and were interspersed with three filler negative emotions (disgust, fear, sadness) not of primary theoretical interest. A 7-point scale (1 = not at all, 7 = very much) accompanied all emotion items.…”
Section: Group-based Emotionsmentioning
confidence: 99%